Plastic Cup Lid Molding Machine Design For Clean Water Ready to Drink in Sumbergedang Village, Pasuruan: Desain Mesin Cetak Tutup Gelas Plastik Untuk Air Bersih Siap Minum di Desa Sumbergedang Pasuruan - Tjahjanti, Prantasi Harmi; Ivanda, Henry Vian; Hamzah, Fuad (Procedia of Social Sciences and Humanities, 2022)
Plastic cup lid printing machine design for clean ready-to- drink water in Sumbergedang Village, Pasuruan is the result of research and dedication to the Community that has been done before. Design it later then it will be made / realized with the main objectives are as follows:additional income for the village community of Sumbergedang Pasuruan. MachineThis plastic cup lid print is designed to use a driving motor, so it's not manual power. The design uses SolidWork software with the input data being the cup sealer machine body component, the motor component for the sealing process, the cutter press component (plastic cutter when sealed), the ring component for the glass cup, and other additional components. The final result of the design made meets the requirements to be made (manufacturing)